Peculiarities of organizational changes’ management on freight transport companies - S. A. Borodulina; N. A. Loginova (Вестник СибАДИ, 2017)
The authors have developed and justified the basis of the effective management of organizational changes on freight transport companies through detaching projections of three types of factors - labor, economic, production - which take into account the sectoral specificity of functioning enterprises. The received results can be used in developing of corresponding methodological foundations.